Inconsistent Patterns of Soil Fauna Biodiversity and Soil Physicochemical Characteristic Along an Urbanization Gradient - Yu, Shiqin; Wu, Zhifeng; Xu, Guoliang; Li, Cheng; Wu, Zhijian; Li, Zengguang; Chen, Xiaohua; Lin, Miaojun; Fang, Xueru; Lin, Yongquan (Frontiers in Ecology and Evolution, 2022)
Urbanization has induced substantial changes in soil physicochemical characteristic, while less is known about how urbanization affects soil fauna biodiversity, and how soil physicochemical changes mediates this effect. Along an urbanization gradient in the city of Guangzhou, we established four sites with different urbanization intensity, including an urban site, two suburban sites and a rural site, and then studied their soil physicochemical characteristic and soil fauna biodiversity. The soil physicochemical characteristic dramatically changed along the urbanization gradient. In contrast, the soil fauna biodiversity exhibited a very different pattern. Soil fauna abundance was highest in the suburban sites, supporting the intermediate disturbance hypothesis. Moreover, there were significant changes of Pielou’s evenness and community structure in the suburban sites, indicating the responses to urbanization was taxonomically dependent. Soil fauna biodiversity in the urban site was similar to the rural site, except that the rural site was characterized by microdrile oligochaetes while the urban site was not characterized by any taxa Our linear and canonical correspondence analysis models suggested that soil physicochemical characteristic only contributed a little to the variance of soil fauna abundance (19%), taxa number (27%) and community structure (12%), and explained about half of the variance in Shannon’s diversity and Pielou’s evenness. However, with urbanization intensity increasing, soil physicochemical changes could both increase and decrease the taxa diversity and evenness. Our results suggest that the effects of urbanization on soil fauna biodiversity is dependent on the urbanization intensity but not simply on whether an ecosystem is urbanized or not. To elucidate the effect of urbanization on soil fauna biodiversity, further studies should quantify urbanization intensity. Further studies should also take other urbanization agents into account and distinguish the effect of each specific soil physicochemical characteristics.